EVALUATION PROGRAM OF REGIONAL TRAINING CENTER (PELATDA) PON XIX SOUTH SULAWESI - Sahabuddin Sahabuddin (Program Pascasarjana Universitas Negeri Jakarta, 2017)
AbstractThe objective of this research is to evaluate Program Regional Training Center (PELATDA) PON XIX South Sulawesi. This is a qualitative and quantitative research with evaluation approach using Context, Input, Process, and Product (CIPP) model. Methods of collecting data in triangulation using questionnaires, interviews, document studies and observation. The result shows that: (1) Context Evaluation: having strong government policies, objectives and targets are well manifested, with an analysis of conditions that need to be improved, as well as a good strategy. (2) Input Evaluation; Excellent athlete and coach resources while for nutrition and medical teams has not been well implemented, funding, transparency and fund accountability need to be improved, adequate facilities and infrastructure support, and good cooperation between stakeholders and provincial branches of sport. (3) Process Evaluation; The training plan is well executed, the implementation of the training still needs to be improved, the nutritional and medical demands are not maximal, and the implementation of evaluation and monitoring still need to be optimally implemented. (4) Product Evaluation; Increasing physical condition, psychology and athletic health, but the medal achievement on PON XIX in West Java did not reach the target charged by Koni South Sulawesi Province. It can be recommended that Regional Training Center Program (PELATDA) PON XIX South Sulawesi is very disappointing because it does not reach the target of rank VI, so it is advisable to build synergy between the Government, Koni and Board of Sport Branch and Private Parties in improving the maximum Sport Achievement in South Sulawesi Province.Keywords: Program Evaluation, Regional Training Center (Pelatda), PON XIX